Phosphorylated Mr 32,000 dopamine- and cAMP-regulated phosphoprotein inhibits Na+,K(+)-ATPase activity in renal tubule cells. - Aperia, A (1991)
Dopamine inhibits Na+,K(+)-ATPase activity in several renal tubule segments and thereby regulates urinary Na+ excretion. We now show that a phosphopeptide of 31 amino acids, corresponding to residues 8-38 of the protein phosphatase inhibitor DARPP-32 (dopamine- and cAMP-regulated phosphoprotein of Mr 32,000), mimics the inhibitory action of dopamine on Na+,K(+)-ATPase activity in renal tubule cells from the ascending limb of the loop of Henle. The dephosphorylated form of the peptide is ineffective. The results indicate that dopamine acts through a protein phosphorylation pathway to regulate the activity of an ion pump. In addition, the data suggest that inhibition of protein phosphatase 1 by phophorylated DARPP-32 is a component of the mechanism by which dopamine regulates urinary Na+ excretion.